Structural and Electronic Properties of Donor-Acceptor Molecular System: B3LYP/ DFT Calculations - Ghalib, Basim Abdullattif (University of Thi-Qar Journal of Science, 2014)
Present work deals with the structural and electronic properties of trifluorocarbon-nitro CF3-NO as a donor-acceptor molecular system. Density functional theory at the three parameters B3LYP level of theory was employed with various basis sets to determine and calculate some structural and electronic properties for this molecular system. The calculations include the geometrical parameters of the studied structures. And some electronic properties of these were investigated include the total energy, electronic states, ionization potential, electron affinity, electro chemical hardness, softness and electrophilic index. The results showed that 6-31G (d, p) level of theory gave good agreement values of geometrical parameters with experimental data in compared with other levels.